Comparative evolution of some minerals, osteocalcin, 25(OH)D and 1,25(OH)2D in the female camel and its newborn in South Morocco - M. El Khasmi; F. Riad; A. Safwate; M. Bengoumi; K. Hidane; M. J. Davicco; V. Coxam; B. Faye; J.P. Barlet (Revue d’Elevage et de Médecine Vétérinaire des Pays Tropicaux, 2000)
Postpartum kinetics of plasma minerals (Ca, P, Mg, Na and K), osteocalcin, 25(OH)D and 1,25(OH)2D were observed in the lactating camel (n = 5) and its newborn (n = 5) in South Morocco. Ca and P plasma levels (mg/l) were higher in camel calves than in dams from birth up to day 30 of life. At birth, Mg, Na and K plasma levels (mg/l) were lower in camel calves than in dams. OC plasma levels (ng/ml) were higher in camel calves than in their mothers from birth (3.4 ± 0.3 vs. 0.7 ± 0.3, P < 0.05) up to day 30 of life (5.2 ± 0.5 vs. 0.7 ± 0.3). These levels reached their maximum at day 3 after birth in camel calves (6.8 ± 0.5) and at day 4 postpartum in dams (2.3 ± 0.4). Plasma levels (pg/ml) for 25(OH)D and 1,25(OH)2D in newborn calves were lower at birth than those in dams (58.2 ± 12.4 vs. 480 ± 59.7, P < 0.05, and 834.8 ± 61.5 vs. 1301 ± 209, P < 0.05, respectively). These neonatal levels became significantly higher compared to those of the dams as early as day 15 after birth for 25(OH)D (176.4 ± 19.6 vs. 116.1 ± 30.4, P < 0.05), and day 7 after birth for 1,25(OH)2D (1215 ± 248 vs. 571 ± 64, P < 0.05). These results show that OC could be a reliable biomarker for neonatal bone growth in camel and that 25(OH)D and 1,25(OH)2D might play a major role in calcium homeostasis regulation in newborn calves and their lactating dams.